2007
DOI: 10.1074/jbc.m611801200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Heat Shock Transcription Factors (HSFs) and Divergent Binding Sequences

Abstract: The target genes of the heat shock transcription factor (HSF) contain a cis-acting sequence, the heat shock element (HSE), which consists of multiple inverted repeats of the sequence 5-nGAAn-3. Using data acquired in this and a previous study, we have identified the HSEs in 59 of 62 target genes of Saccharomyces cerevisiae Hsf1. The Hsf1 protein recognizes continuous and discontinuous repeats of the nGAAn unit; the nucleotide sequences and configuration of the units diverge slightly among functional HSEs. When… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 63 publications
2
46
0
Order By: Relevance
“…Sakurai and Takemori (2007) noted that targets of HSF included cis-HSE sequences, which are the reverse repetitive sequences of multiple 5'-nGAAn-3'. HSF binding to HSEs is very important in HSP gene transcription, indicating that HSP gene transcription is regulated by the HSF gene.…”
Section: Discussionmentioning
confidence: 99%
“…Sakurai and Takemori (2007) noted that targets of HSF included cis-HSE sequences, which are the reverse repetitive sequences of multiple 5'-nGAAn-3'. HSF binding to HSEs is very important in HSP gene transcription, indicating that HSP gene transcription is regulated by the HSF gene.…”
Section: Discussionmentioning
confidence: 99%
“…It has beeen reported that the HSE and its binding protein heat shock transcription factor are highly conserved from yeast to humans. [19][20][21] It is well known that heat shock and hydrogen peroxide induces catalase gene expression in Aspergilli 5,[22][23][24] and other species, [6][7][8]25) and that each catalase gene promoter has regulatory element for stress response. But the regulatory elements are different in species.…”
Section: Discussionmentioning
confidence: 99%
“…To test for the effects of riluzole on the turnover/decay of the 35 S-labeled cellular proteins, it was added to designated plates to a final concentration of 2 M at the beginning of the chase. Aliquots (in quadruplicate) of the cell culture medium were removed at 2, 4, 6, and 24 h after initiation of the chase, and the amount of trichloroacetic acid soluble radioactivity was determined according to published methods (19).…”
Section: Methodsmentioning
confidence: 99%
“…GLT1 was probed with either sc-15317 (1:200 dilution; SCBT) or ab61859 (1:500 dilution; Abcam); both gave similar results, although the Abcam antibody gave a lower background. To affirm even loading of protein, membrane was co-probed for actin (42 kDa) 35 S-labeled HSF1, it was added to designated plates to a final concentration of 2 M at the beginning of the chase. Cells were harvested at 0, 4,8,12, and 24 h after initiation of the chase in the absence versus the presence of 2 M riluzole.…”
Section: Methodsmentioning
confidence: 99%